Kekerasan Seksual Berbasis Elektronik: Permasalahan dan Respons terhadap Kasus - antik bintari (Jurnal Perempuan, 2024)
Cyber sexual harassment is a common and dangerous form of aggression perpetrated against women, yet little attention has been paid to attitudes related to sexual violence in cyberspace. The increase in violence against women, including sexual violence in cyberspace, has become a global concern; this increase is in line with the development of social media in Indonesia. There is new hope since the enactment of Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (UU TPKS), which is expected to provide guarantees of prevention, protection, access to justice and recovery, as well as comprehensive fulfillment of victims’ rights which have never been obtained until now. It is hoped that this policy will also serve as a legal framework to address cybersexual violence. However, after almost two years of having passed the TPKS Law, this regulation’s implementation still faces challenges. It is not yet optimal in handling cyber sexual violence, which tends to be considered an act of sexual violence with new methods and means in line with current technological developments. This article discusses the current phenomenon of cyber sexual harassment and further explores the response of the Indonesian state/government to this phenomenon, along with its opportunities and challenges.